Taxonomy, Typification and distribution of Thyrsia zea (Poaceae) - Chorghe, Alok R.; Halder, Suman; Kulloli, R.n. (Phytotaxa, 2023)
The nomenclature of the name Thyrsia zea has been discussed here along with the second step lectotypification. Taxonomy and distribution of Thyrsia zea in India and its relation with the two closely related African species are also discussed in this paper.